CHARLES DICKENS AS A SOCIAL NOVELIST: LIFE EXPERIENCE AND LITERARY DEVELOPMENT - Izzatilloyeva Mohichehra Baxtiyorovna (TADQIQOTLAR, 2026)
Abstract. Charles Dickens occupies a central place in Victorian literature as a novelist who transformed personal hardship into powerful social commentary. This article examines Dickens’s development as a social novelist through the interaction of his life experience and literary evolution. Drawing on his early encounters with poverty, child labor, and institutional injustice, Dickens created a body of fiction that exposes social inequalities while appealing to moral responsibility and human compassion. The study analyzes how Dickens’s biography influenced his thematic concerns, narrative techniques, and reformist vision, highlighting his role in shaping the social conscience of nineteenth-century England.